Regulador vegetal e bioestimulante na indução floral do maracujazeiro-amarelo em condições de entressafra - Ataíde, Elma Machado; Ruggiero, Carlos [UNESP]; Rodrigues, João Domingos [UNESP]; Oliveira, João Carlos de [UNESP]; Rodrigues, Teresinha de Jesus Déleo [UNESP]; Silva, José Rafael da (Sociedade Brasileira de Fruticultura, 2006)
O objetivo do trabalho foi avaliar o efeito de regulador vegetal e de bioestimulante na indução floral do maracujazeiro-amarelo em condições não-indutivas, em Araguari-MG. Foram identificados e podados 12 ramos terciários por parcela (02-04-05), sendo 6 deles expostos de um lado da espaldeira, com luminosidade predominante pela manhã e 6 do outro lado da espaldeira, com luminosidade à tarde. O delineamento experimental foi em parcelas subdivididas, com 7 tratamentos principais (parcelas): 0mg L-1 (testemunha); 100mg L-1; 200mg L-1 e 300mg L-1 de regulador vegetal GA3 (i.a.); 2,08 mL L-1; 4,17mL L-1 e 6,25mL L-1 de bioestimulante Stimulate® (i.a.), em duas aplicações foliares (09-04-02 e 09-05-02), acrescidas de espalhante adesivo Silwett® a 0,05%. Além desses, foram utilizados 2 tratamentos secundários (subparcelas): exposição dos ramos à luminosidade da manhã e da tarde, com 4 repetições de 3 plantas por parcela. Cada subparcela foi um dos dois lados da espaldeira. As médias foram comparadas pelo teste de Tukey, a 5% de probabilidade. Realizou-se, aos 75 dias, a avaliação nos dois lados da espaldeira do comprimento dos ramos e entrenós, número de nós, de folhas e de botões florais. As variáveis estudadas não foram influenciadas pelo uso de GA3 e Stimulate®, no entanto houve diferença quando os ramos ficaram expostos à luminosidade da manhã em relação àqueles com luminosidade à tarde.

The objective of the present work was to evaluate the effect of plant regulator and biostimulant in the floral induction of yellow passion-fruit under non inductive conditions in Araguari-MG. Twelve tertiary branches were identified and trimmed per plot (04/02/04), whereas six were exposed, on one side of the supporting stick, with predominant luminosity during the morning and six on the other side of the supporting stick, with luminosity during the evening. The experimental design was subdivided plots, with main treatments (plots): 0mg L-1 (control); 100mg L-1; 200mg L-1 and 300mg L-1 of plant regulator GA3 (i.a.); 2.08 mL L-1; 4,17mL L-1 and 6.25mL L-1 of StimulateTM biostimutant (i.a.), in two leaf applications (04/09/02 e 05/09/02), supplemented with SilwettTM adhesive spread at 0.05%. Besides those treatments, secondary treatments were used (subplots): exposition of the branches to morning and evening light, with four repetitions and three plants per plot. Each subplot was one of the sides of the supporting stick. The data was submitted to the analysis of variance. In both sides of the supporting stick, the length of the branches and internodes, the numbers of nodes, of leaves and of floral buds were evaluated at 75 days after the first application of the treatments. The variables studied were not influenced by the use of GA3 and StimulateTM, however, there was difference when the branches were exposed to morning light in relationship to those exposed to evening light.
Plant regulator and biostimulant in yellow passion-fruit floral induction under non inductive condition
Keywords: flowering; gibberelin; Passiflora edulis Sims f. flavicarpa; Stimulate; Florescimento; Giberelina; Passiflora edulis Sims f. flavicarpa; stimulate